Chronic Asymptomatic Pancreatic Hyperenzymemia: A Long-term Follow-up. Issue 4 (April 2019) - Amodio, Antonio; De Marchi, Giulia; Granato, Anna; de Pretis, Nicolò; Gabbrielli, Armando; Manfredi, Riccardo; Pozzi Mucelli, Roberto; Frulloni, Luca
Abstract : Objectives: Chronic asymptomatic pancreatic hyperenzymemia (CAPH) was described as a benign disease. However, we already described clinically relevant findings requiring surgery or follow-up in half of the subjects. The aim of this study was to evaluate the long-term outcome of CAPH in terms of symptoms and evolution toward chronic pancreatitis. Methods: Subjects previously enrolled in the first phase of the study (from 2005 to 2010) were reinvestigated from December 2013 to January 2017 with a phone call ± magnetic resonance cholangiopancreatography with secretin stimulation. Results: A total of 133 subjects were eligible for the follow-up study (75 males, 58 females; age, 48.4 [standard deviation SD, 14] years); 24 (18%) of them dropped out. During a mean follow-up of 9.3 (SD, 5.2) years after the first diagnosis of CAPH, no episode of acute pancreatitis or abdominal pain was reported. Sixty-three subjects (58%) of 109 underwent magnetic resonance cholangiopancreatography with secretin stimulation with a mean follow-up of 5.7 [SD, 3.1] years (range, 1–11 years). Secretin stimulation-MRCP resulted unchanged in 54 (90%) of 60 subjects, worsened in 3 (5%) and improved in 3 (5%). Two subjects died from causes unrelated to pancreatic disease. Conclusions: Excluding subjects with a pancreatic disease at index magnetic resonance imaging, CAPH is a benign condition.